Are libraries obsolete? an argument for relevance in the digital age - Herring, Mark Y.,1952- (McFarland & Company, Inc., Publishers, 2014)
"The digital age has transformed information access in ways that no one ever dreamed. But the afterclap of our digital wonders has left libraries reeling as they are no longer the chief contender in information delivery. The book explores how libraries and librarians must face the future if they are to continue to be relevant, vibrant, and enduring"--Provided by publisher